Effect of daily and weekly testing on students mathematics achievement at upper basic level (2009)
Assessment is a systematic basis for making inference about the learning and development of students towards increasing students' learning and development. Teachers should therefore realize that assessment is the quickest strategy to improve student learning, hence this study examined an assessment strategy on Upper Basis School Mathematics achievement. The subjects in this study were upper basic school students from four Mathematics classes. All the students were taught by the same teacher, and the experimental duration was for three months or equivalent of one term. The four classes comprise two control groups and two experimental groups. In the control group, students took weekly tests every Friday, and in the experimental groups, students took daily tests during the last twelve minutes of the stipulated forty-five minutes allowed per period of the class teaching. The researcher examined whether the daily tests had significant impact on students' mathematics achievements as measured at the end of term examination. The researcher also examined whether daily testing had any effect on students' homework grades. The study found that daily testing significantly improved students' mathematics grades/score and home work grades.